ANALISIS PENGARUH PRICE EARNING RATIO, DIVIDEN PAY OUT RATIO, DAN RETURN ON EQUITY TERHADAP STOCK PRICE PADA INDUSTRI CONSUMER GOOD DI BURSA EFEK INDONESIA TAHUN 2007- 2010 - FURI ARINTA (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
The Investors must have a careful analysis,through, and support of accurate data to reduce the risk for investo who investor. Analysis fundamental as a technique used by investors to find information about company’s financial report. Some of important component analysis the company’s fundamental is Price Earning Ratio (PER), Dividen Pay Out Ratio (DPR)dan Return On Equity (ROE). Consumer Good industry is the one of growing industry in Indonesia quite well with products witch existence is a primary requirement for fulfilling the requirement. The study aims to analysis the effect of variable Price Earning Ratio(PER), Dividen Pay Out Ratio (DPR), and Return On Equity (ROE) of Stock Price on Consumer Good Industry in Indonesia Stock Exchange in 2007-2010.Analysis method used are research relationship and methods of statistical analysis using multiple linier regression analysis, partial and simultaneous significant testing.A partially variable PER has no significant effect on stock price, a partially DPR has a significant effect on stock price,and a partially variable ROE has a significant effect on stock price of Consumer Good Industry. While simultaneously the three variables have a significant effect.